Organocatalytic Approach to Functional Semifluorinated Polymers Driven by Visible Light. Issue 15 (13th June 2018) - Xu, Tianchi; Tu, Kai; Cheng, Jiannan; Ni, Yuanyuan; Zhang, Lifen; Cheng, Zhenping; Zhu, Xiulin
Abstract: Through the construction of an organic photocatalysis system, photoredox catalyst (PC)/additive, where PC stands for photoredox catalyst, an organocatalyzed step transfer‐addition and radical‐termination (O‐START) polymerization irradiated by blue LED light at room temperature is realized. Different types of α, ω‐diiodoperfluoroalkane A and α, ω‐unconjugated diene B are copolymerized through O‐START efficiently, and generate various kinds of functional semifluorinated polymers, including polyolefins and polyesters. The process is affected by several factors; solvents, additives, and feed ratio of A to B. After optimization of all these components, the polymerization efficiency is greatly improved, generating polymers with both relatively high yield and molecular weight. Considering the mild reaction condition, easy operation process, and free‐of‐metal‐catalyst residues in the polymer product, the organocatalytic polymerization strategy provides a simple and efficient approach to functional semifluorinated polymer materials and hopefully opens up their application in high‐tech fields. Abstract : Organocatalyzed copolymerization of α, ω‐diiodoperfluoroalkanes A with α, ω‐unconjugated dienes B is successfully realized for the preparation of various functional semifluorinated polymers (AB)n under irradiation with blue LED light at room temperature, which facilitates new applications of the final polymer product (AB)n .